Reform program in developing countries: higher education reform and accountability in Mozambique - Gomana, Bernardete Sebastiao (AUC Knowledge Fountain, 2012)
The present research deals with the question of education in Mozambique. It is an analysis on the tertiary education or higher education sub-sector. Considering the importance of this sub-sector to the economic and social development, the reform undertaken to address the deficiencies in education sector is one of the main tools of analysis. In fact, in the wave of African reforms, Mozambique introduced reforms at different levels of society, and higher education is considered as one of the government's priority. Therefore, to analyze and assess the reforms in higher education, the research uses the expansion of education physically and quality, and the access and equity. In the study, the data were collected from the Ministry of Education and Culture in Mozambique. Those data were analyzed taking into consideration the Strategic Plan for Higher Education (SPHE) 2000-2010. SPHE is another main reference of the study. The time frame of the study is 2003 to 2007 due to the data availability. The results should be considered as being partial ones, because not all objectives of this plan were analyzed. The findings show that there is an improvement in higher education based on the expansion of higher education institutions, access and equity. From 9 higher education institutions in 2001, there are more than 40 institutions and all 11 provinces are covered. Moreover, the access improved, but there is a need to improve female participation as well. The improvement verified brings other challenges for quality improvement and investment. Government responsiveness is one of the factors for the success of reform program. Mozambique's government should consider the process of reform as a continuous one.